Categorization of the cultural content of EFL textbooks: review - Obaid, Ali Abdulridha; Othman, Moomala; Aralas, Dalia; Mansor, Nor Shahila (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
In recent years there has been a growing interest in studying culture integration in English as foreign language textbooks. This can be attributed, inter alia, to both the sensitivity of tackling people’s cultures in textbooks which maintain an outstanding position in the teaching / learning process, and to rapidly increasing importance English has gained within the world of globalization. In the TESOL field, researchers examine and then categorize the cultural representations when analyzing the content of EFL textbooks, adopting or adapting different frameworks in the available literature. This paper screens the theoretical literature that addresses the cultural content of EFL textbooks in TESOL studies highlighting the most dominant frames of analysis to classify the cultural representations of the content of textbook as cultural categories (types), dimensions as well as themes, to hopefully provide a reasonable platform for scholars to rely on. Particularly concerning the cultural types, the issue is more problematized within an argument. The review does not then touch upon neither the intercultural or multicultural elements nor other approaches of analysis from fields other than TESOL such as Applied Linguistics or Discourse Analysis. It concludes that literature – based terminologies are better employed for categories, and show that, for the sake of in-depth analysis, studies usually consolidate a framework consisting of a model for cultural dimensions or one for cultural themes together with a general model for types.